2019
DOI: 10.1634/theoncologist.2019-0063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Copy Number Variations in Oral Cavity Squamous Cell Carcinoma Reveals a Novel Role for MLLT3 in Cell Invasiveness

Abstract: Background. DNA copy number variations (CNVs) are a hallmark of cancer, and the current study aimed to demonstrate the profile of the CNVs for oral cavity squamous cell carcinoma (OSCC) and elucidate the clinicopathological associations and molecular mechanisms of a potential marker derived from CNVs, mixed-lineage leukemia translocated to chromosome 3 protein (MLLT3), in OSCC carcinogenesis. Materials and Methods. CNVs in 37 OSCC tissue specimens were analyzed using a high-resolution microarray, the OncoScan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 75 publications
3
13
0
Order By: Relevance
“…Moreover, it was shown that DOT1L participates in the upregulation of the cytoskeleton regulator RhoGTPase (RhoC) and of cIAP-2 and XIAP, belonging to the family of inhibitors of the apoptosis (IAPs), and facilitates invasion potential and cisplatin resistance of CD44v3 high ALDH1 high cells ( Bourguignon et al, 2016 ). In an additional study, amplification and upregulation of MLLT3 gene was found in oral cavity squamous cell carcinoma (OSCC) cells, where this gene has been involved in cell migration and invasion in conjunction with DOT1L association and regulation of CITED4 gene promoter and dysregulation of HIF-1α target genes TWIST , MMP1 , MMP2 , VIM , and CDH1 ( Wang C. I. et al, 2019 ).…”
Section: Mechanisms Of Dot1 Action In Solid Tumorsmentioning
confidence: 99%
“…Moreover, it was shown that DOT1L participates in the upregulation of the cytoskeleton regulator RhoGTPase (RhoC) and of cIAP-2 and XIAP, belonging to the family of inhibitors of the apoptosis (IAPs), and facilitates invasion potential and cisplatin resistance of CD44v3 high ALDH1 high cells ( Bourguignon et al, 2016 ). In an additional study, amplification and upregulation of MLLT3 gene was found in oral cavity squamous cell carcinoma (OSCC) cells, where this gene has been involved in cell migration and invasion in conjunction with DOT1L association and regulation of CITED4 gene promoter and dysregulation of HIF-1α target genes TWIST , MMP1 , MMP2 , VIM , and CDH1 ( Wang C. I. et al, 2019 ).…”
Section: Mechanisms Of Dot1 Action In Solid Tumorsmentioning
confidence: 99%
“…Mutations in CBP and cofactor EP300 can significantly disrupt the overall CBP acetyltransferase activity, resulting in abnormal downregulation of target genes and leukaemia outbreak 12 . Furthermore, it has been demonstrated that abnormal copy number variation of transcriptional cofactors such as MLLT3 contributes to the overall activity of the oncogenic transcription complex 43 . More importantly, understanding these cofactor abnormalities provides therapeutic opportunities for blocking oncogenic TF transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition, MLLT3 mutations are associated with neurodevelopmental disease including mental retardation, epilepsy and ataxia, 16,17 and MLLT3 overexpression is associated with a poor prognosis in oral cavity squamous cell carcinoma. 18 MLLT3 is highly expressed in hematopoietic stem cells (HSCs) and erythroid/megakaryocytic (E/Meg) compartments in humans and in mice. 19,20 Previous in-vitro studies documented an essential role of MLLT3 in HSC stemness maintenance 21 and erythroid/megakaryocytic (E/Meg) lineage decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The two genes are involved in a reciprocal in‐frame translocation—t(9;11)(p22;q23)—resulting in an oncogenic KMT2A‐MLLT3 fusion protein, which induces leukemia transformation in murine models 14,15 . In addition, MLLT3 mutations are associated with neurodevelopmental disease including mental retardation, epilepsy and ataxia, 16,17 and MLLT3 overexpression is associated with a poor prognosis in oral cavity squamous cell carcinoma 18 …”
Section: Introductionmentioning
confidence: 99%